A Procedural and Educational Experience Following Creation of an Advanced Pediatric Endoscopy Service. Issue 4 (April 2017) - Mezoff, Ethan A.; Lin, Tom K.; Kaul, Ajay; Kocoshis, Samuel; Putnam, Phil; Pentiuk, Scott
Abstract : ABSTRACT: Advanced endoscopic procedures occur infrequently enough in pediatric patients to preclude effective maintenance of competence among all pediatric gastroenterologists. A recent study suggests that fellows are largely unable to achieve the prescribed case volume recommended to achieve competence. We sought to describe the procedural and educational experience following the creation of an advanced pediatric endoscopy service in response to declining confidence among practice members regarding advanced procedures. We found most advanced endoscopy cases (90%) were accomplished during routine business hours with little seasonal variation. Esophageal dilations occurred far more than all other procedures provided by this service. Control of nonvariceal bleeding, feeding tube placement, enteroscopy, and needle knife therapy, among others, were performed exclusively but relatively infrequently by members of this advanced endoscopy service. Fellows were present for many cases, although they participated in relatively few. We conclude that the creation of an advanced endoscopy service permits distillation of rare but technically demanding cases to few providers, ensuring maintenance of skills, although the role of fellows remains in question. Abstract : Supplemental Digital Content is available in the text